TINGKAT PENGETAHUAN DAN KEJADIAN SKABIES DI PONDOK PESANTREN - Wahyu Dewi Sulistyarini; Hamka .; Zaitun Sholehah (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
Scabies is a disease related to personal hygiene. The incidence of scabies is often found in environments with high occupancy and interpersonal contact density such as prisons, orphanages, and Islamic boarding schools. This is caused by several factors, one of which is the lack of knowledge about scabies. Lack of knowledge about the dangers of scabies makes this disease considered an ordinary disease because it does not endanger lives. To find out whether there is a relationship between the level of knowledge and the occurrence of scabies in the Al-Izzah Islamic boarding school. This research is descriptive analytic, with cross sectional design. Conducted in April-May 2018, the sample of this study amounted to 56 respondents. The results of the statistical test are based on data analysis using Chi Square test Obtained results (Value P = 0.000> 0.005). The results of the research conducted by the researcher showed that there was a relationship between the knowledge of santri and the incidence of scabies at the Al-Izzah Simpang Pasir Palaran Islamic Boarding School.